Sinusitis Treatment Guideline Adherence in the e-visit Setting - Smith, Kevin L.; Tran, Dang; Westra, Bonnie L. (Applied Clinical Informatics, 2016)
Studies demonstrate poor guideline adherence by health care providers for the treatment of upper respiratory infections, particularly acute bacterial rhinosinusitis (ABRS), in the appropriate prescribing of antibiotic medications.The purpose of this quality improvement project was to evaluate the effect of implementing interventions for improving adherence to a clinical practice guideline for the management of ABRS for patients treated in the e-visit setting. Interventions included: providing a report to providers of their adherence to the ABRS clinical guideline prior to the intervention, providing updated education on the ABRS guideline, and implementing a clinical decision support system reminder.A pre and post intervention evaluation design was used. Data were obtained from a retrospective electronic health record (EHR) data extract of all 316 diagnoses for ABRS in the preintervention 2-month time period and all 368 diagnoses of ABRS in the post-intervention 2-month time period. A review of the structured clinical data elements was performed to determine whether the provider adhered to the clinical guideline, meaning that only patients meeting the criteria for ABRS were to receive an antibiotic prescription.The interventions resulted in a 3.3% improvement in adherence to the ABRS clinical guideline from 95.25% adherence pre-intervention to 98.4% post-intervention. These results demonstrated that the use of an educational intervention and clinical decision support resulted in improved adherence to the ABRS clinical guideline in the e-visit setting. The implications for practice could be significant in that these quality improvement interventions improve guideline adherence and reduce unnecessary prescribing of antibiotics.
Keywords: Clinical decision support systems; guideline adherence; quality improvement; acute bacterial rhinosinusitis (ABRS); e-visit; informatics